Utilization of antenatal ultrasound scan and implications for caesarean section: a cross-sectional study in rural Eastern China - Huang, Kun (BioMed Central, 2012)
BACKGROUND: Antenatal ultrasound scan is a widely accepted component of antenatal care. Studies have looked at the relationship between ultrasound scanning and caesarean section (CS) in certain groups of women in China. However, there are limited data on the utilization of antenatal ultrasound scanning in the general population, including its association with CS. The purpose of this study is to describe the utilization of antenatal ultrasound screening in rural Eastern China and to explore the association between antenatal ultrasound scan and uptake of CS. METHODS: Based on a cluster randomized sample, a total of 2326 women with childbirth participated in the study. A household survey was conducted to collect socio-economic information, obstetric history and utilization of maternal health services. RESULTS: Coverage of antenatal care was 96.8% (2251/2326). During antenatal care, 96.1% (2164/2251) women received ultrasound screening and the reported average number was 2.55. 46.8% women received at least 3 ultrasound scans and the maximum number reached 11. The CS rate was found to be 54.8% (1275/2326). After adjusting for socio-demographic and clinical variables, it showed a statistically significant association between antenatal ultrasound scans and uptake of CS by multivariate logistic regression model. High husband education level, high maternal age, having previous adverse pregnant outcome and pregnancy complications during the index pregnancy were also found to be risk factors of choosing a CS. CONCLUSIONS: A high use of antenatal ultrasound scan in rural Eastern China is found and is influenced by socio-demographic and clinical factors. Evidence-based guidelines for antenatal ultrasound scans need to be developed and disseminated to clinicians including physicians, nurses and sonographers. Guidance about the appropriate use of ultrasound scans should also be shared with women in order to discourage unreasonable expectations and demands. It is important to monitor the use of antenatal ultrasound scan as well as the indications for caesarean section in rural China.